Utilising computational power to improve drug safety: predicting and understanding tissue selectivity - Vlot, Anna (Student Undergraduate Research E-journal!, 2016)
Increasing tissue selectivity of compounds may aid the development of safer drug treatments by decreasing side effect prevalence. To enable this, improved insight into the mechanisms underlying tissue selectivity is required. In this article the influence of receptor concentration, drug-target affinity and binding kinetics on tissue selectivity is described. Simulations were performed in a physiological model with drug-target binding, informed by in silico predicted physicochemical properties. Lower tissue selectivity was observed for high affinity ligands than for low affinity ligands. This observation moves against the current paradigm in which high affinity ligands are assumed to be better drug candidates.